Risk factors for non-steroidal anti-inflammatory drugs - Moura, Sandro Carlos da Conceição (2022)
Pain is a complex and subjective phenomenon, and one of the main reasons for attending physicians. For this reason and for the expenses involved, it is a public health issue, which must be conducted by an interdisciplinary team, aiming at the use of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs). The present study aimed to identify risk factors in the traditional use of non-steroidal anti-inflammatory drugs in riverside communities: paracetamol-x dipyrone. This research refers to a literature review, carried out from 2012 to 2022, based on consultations in journals, articles indexed in the SciELO, LILACS, Medline and PUBMED databases, books and websites of official entities such as the Ministry of Health (MS) and the World Health Organization (WHO). In a context where paracetamol and dipyrone are spontaneously available, part of the Amazon riverside population has been self-medicating, the main reason being pain of different origins, flu-like symptoms (cough and fever), infections and pain problems, the main factors of risk is the non-search for health services and the natural habit of taking medication. NSAIDs provide a considerable satisfaction rate among riverside communities, however, it is necessary to provide guidance from the pharmacist in providing the necessary information for the prescriber to make the appropriate choice of analgesic.